ANALISIS PERBANDINGAN METODE PENDUKUNG KEPUTUSAN PEMILIHAN SKINCARE MENGGUNAKAN METODE SAW, WP, dan SMART - Nuraeni, Yayang Ayu; Nurjanah, Noneng; Hendrawan, Satya Arisena; Muhiban, Ayi (TRANSFORMASI, 2025)
Increasing public awareness of the importance of skin care to maintain health has encouraged the emergence of various products on the market. In recent years, the skincare industry has experienced very rapid growth. This study aims to enable users to choose skincare that is safe, appropriate, and in accordance with their facial skin type with the methods used being Simple Additive Weighting (SAW), Weighted Product (WP), and Simple Multi-Attribute Rating (SMART). The results of the calculation process based on the level of suitability, it was found that using the SAW and SMART methods was better than the WP method, namely with a percentage value of suitability between 99.85719% in the SAW method, 99.85715% in the WP method, and 99.85715% in the SMART method. So the SAW and SMART methods are the most relevant methods to solve the problem of providing loans.Keywords : Skincare, Simple Additive Weighting, Weighted Product, Simple Multi-Attribute Rating, Decision Support System.